Sheltering is not gathering: A study with groups of siblings in institutional sheltering - Taborda, Lígia Negrão Costa; Magalhães, Celina Maria Colino (Advances in Social Sciences Research Journal, 2019)
Objective: To describe and analyze the interactions between children and their siblings in an institutional shelter. Method: Descriptive research with convenience sample carried out with seven groups of two or three siblings who were at the institution. Focal-subject observation techniques were used with focus on the siblings, noting the frequency, peers, and types of interaction among the siblings and other children. Results: There was a higher average interaction among siblings when they shared the dormitory; when they were in separate ones the interaction was higher with other children. The most common interaction categories were similarity, cooperation, and sharing for the peers in the same bedroom. Conclusion: The sheltering of siblings must have as main principle the maintenance of social and family bonds by strengthening the possibilities of interaction among them and their affective relationships. The simple gathering of siblings alone is not enough to guarantee such fact.